The accuracy of quantitative parameters in 99mTc‐MAG3 dynamic renography: a national audit based on virtual image data. (28th October 2014) - Brolin, Gustav; Edenbrandt, Lars; Granerus, Göran; Olsson, Anna; Afzelius, David; Gustafsson, Agneta; Jonsson, Cathrine; Hagerman, Jessica; Johansson, Lena; Riklund, Katrine; Ljungberg, Michael
Summary: Assessment of image analysis methods and computer software used in 99m Tc‐MAG3 dynamic renography is important to ensure reliable study results and ultimately the best possible care for patients. In this work, we present a national multicentre study of the quantification accuracy in 99m Tc‐MAG3 renography, utilizing virtual dynamic scintigraphic data obtained by Monte Carlo‐simulated scintillation camera imaging of digital phantoms with time‐varying activity distributions. Three digital phantom studies were distributed to the participating departments, and quantitative evaluation was performed with standard clinical software according to local routines. The differential renal function (DRF) and time to maximum renal activity ( T max ) were reported by 21 of the 28 Swedish departments performing 99m Tc‐MAG3 studies as of 2012. The reported DRF estimates showed a significantly lower precision for the phantom with impaired renal uptake than for the phantom with normal uptake. The T max estimates showed a similar trend, but the difference was only significant for the right kidney. There was a significant bias in the measured DRF for all phantoms caused by different positions of the left and right kidney in the anterior–posterior direction. In conclusion, this study shows that virtual scintigraphic studies are applicable for quality assurance and that there is a considerable uncertainty associated with standard quantitative parameters in dynamic 99m Tc‐MAG3 renography, especially for patients with impaired renal function.